EDUKASI SEHAT TERHADAP PENINGKATAN PENGETAHUAN PENCEGAHAN DIABETES PADA LANSIA PROLANIS PUSKESMAS MODOPURO KABUPATEN MOJOKERTO - Ananda Rigi Aditya; Atik Sri Wulandari; Wike Herawaty; Gegel Purnomo Wicaksono; Mochammad Mirza Arif Pranata; Deby Rahmayanti; Dordya Paquita Wijaya; Zahrah Aswa Ananta; Sella Dela Hanna Putri Aziz; Christin Merlina Wattimury; Alya Rosyidah Putri Ramadhani; Sukma Sahadewa (PT. Hasba Edukasi Mandiri, 2026)
Diabetes Mellitus (DM) among older adults is a growing public health problem and is associated with a high risk of serious complications. Limited knowledge and awareness regarding DM management contribute to suboptimal disease control. The SEHAT program (Strategi Hidup untuk Cegah Diabetes) is a simple and effective educational approach to improve awareness of chronic disease prevention among older adults. Objective: To determine the improvement in knowledge of PROLANIS participants regarding diabetes prevention through SEHAT education. Methods: Health education was conducted on February 14, 2026, using leaflet media. Knowledge assessment was performed using a five-item questionnaire administered before and after the educational session to 50 elderly participants. Results: The mean pre-test score was 72.8 and increased to 82.6 in the post-test, indicating a 24% improvement in knowledge. Participants showed high enthusiasm during the educational session. Conclusion: SEHAT education was effective in improving knowledge related to diabetes prevention among older adults.